PEMBUATAN EKSTRAK SEREH (Cymbopogon nardus L.) DALAM SEDIAAN LOTIO - Nurjannah Bachri; Nursalma Nursalma; Natalia Nora (As-Syifaa Jurnal Farmasi, 2015)
This experiment research have been conducted in the pharmaceutical technology laboratory, it aims of making the pharmaceutical in the form of latio of citronella extracts. This research used citronella as samples that are created macerationally and produced a thick extract. The making of lotio used smelting method, namely oil phase smelting and water phase smelting. It was done by observation in organoleptic to see the stability of lotio. Based on the observations result obtained that extracts of (Cymbopogon nardus L.) can be formulated in the latio and physically stable.